Analisis Semiotika Pada Film Series Gadis Kretek Terhadap Representasi Gender - Azura, Sylvia; Rohani, Laila (eScience Humanity Journal, 2024)
Currently, there are still many Indonesian people who apply patriarchal culture, so this can be used as the main topic for making literary works such as films. The researcher decided to make the Film Series "Gadis Kretek" as a medium to convey gender representation. The purpose of this research is to find out how this film can be a mirror on culture and history to influence gender representation in a certain context and how patriarchal values or gender equality are reflected in the narrative and visuals of this film. The research method used in this research is descriptive qualitative. This research uses Hongwei Bao's Queer Theory based on a semiotic approach. Queer theory seeks to reveal that gender and sexuality are not only determined by biology, but also by social and cultural constructions. Based on this research, it can be concluded that women are considered unfit to have greater goals or interests and women are also considered as weak objects.